A Study of Brazilian Postgraduate Patent Applications: Period 2013-2017 - Alves, Vívian Costa; Neves de Oliveira, Bruno César; Santos Pacheco, Roberto Carlos (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2019)
In order to perceive the knowledge production of a country, one can analyze the indicators generated from its stricto sensu postgraduate system. This paper aims to analyze the patent applications required by Brazilian graduate programs between 2013 and 2017 in order to identify the areas of knowledge, the states, regions and programs that have most yielded technology and contributed to the Brazilian innovation system. Thus, a bibliographic survey was carried out concerning the Brazilian postgraduate programs and a quantitative study was conducted using open governmental data published by Capes (Coordination for the Improvement of Higher Education Personnel).